2013
DOI: 10.1590/s1516-35982013000500004
|View full text |Cite
|
Sign up to set email alerts
|

Ractopamine levels on performance, carcass characteristics and quality of pig meat

Abstract: -This study evaluated the effect of ractopamine (RAC) on the performance of finishing pigs and the meat quality of these animals. Seventy crossbred pigs (35 barrows and 35 females) selected for high gain of lean meat, with initial weight of 77.1±0.32 kg were distributed in randomized blocks with five treatments (0, 5, 10, 15, and 20 ppm RAC in the diet) and seven replications during 28 days. The experimental unit was represented by a male and a female pig. Regarding the performance variables, there was a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
3
9
0
8
Order By: Relevance
“…Agric. v.75, n.3, p.197-207, May/June 2018 samples were less red for all RAC inclusion levels (from 5 to 15 mg kg -1 ), although in lightness all RAC levels were identical to the control samples, which is in agreement with most recent studies (Athayde et al, 2012;Garbossa et al, 2013;Lowe et al, 2014;Elsbernd et al, 2015).…”
Section: Quality Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Agric. v.75, n.3, p.197-207, May/June 2018 samples were less red for all RAC inclusion levels (from 5 to 15 mg kg -1 ), although in lightness all RAC levels were identical to the control samples, which is in agreement with most recent studies (Athayde et al, 2012;Garbossa et al, 2013;Lowe et al, 2014;Elsbernd et al, 2015).…”
Section: Quality Parameterssupporting
confidence: 90%
“…A decrease was observed in yellowness (b*) associated with immunocastration, but no effect of RAC for this parameter. As mentioned by Garbossa et al (2013), changes in b* value may be attributed to carotenoid pigments deposited in fat and also to fatty acid composition changes in IMF; in our study both loin yellowness and IMF decreased for IC pigs. As related by Apple et al (2007), even if differences in pork color are reported, they are usually not visibly noticeable by consumers.…”
Section: Quality Parameterssupporting
confidence: 69%
See 1 more Smart Citation
“…O consumo de ração médio diário (CRMD) não foi influenciado pelos níveis de ractopamina adicionados nas dietas. Bridi et al (2008), Ferreira et al (2011), Garbossa (2013 e Marinho et al (2007b), estudando a ractopamina em dietas para suínos em terminação, também observaram que este aditivo não afetou o consumo. O consumo de ração médio diário por suínos depende do nível energético da ração e, como todas as rações foram isocalóricas, já era esperado um consumo de ração médio diário semelhante.…”
Section: Methodsunclassified
“…After genotyping, ten gilts of each genotype within breeds were slaughtered for carcass and meat quality traits testing according to genotype (9)(10)(11). Ultimately, a total of 90 pigs of three genotypes within three pig breeds were slaughtered.…”
Section: Measurements Of Carcass and Meat Quality Traitsmentioning
confidence: 99%